Scheduling in the South African construction industry - Rudzinske, Paul Eric (My University, 1989)
This research report investigates the use and sophistication of scheduling by the South African construction industry, by means of a postal survey and personal interviews. Furthermore, the construction industry's past and present use of scheduling is comparatively analyzed with that of selected overseas countries. A brief description of the various scheduling techniques is provided, together with the histories of these techniques. The primary conclusion of the research work was that the larger companies showed greater dedication to their scheduling, as well as implementing more advanced scheduling techniques. The emergence of cheaper computer systems showed definite impacts on the sophistication and effectiveness of scheduling, and indications of future impacts by computers were also found. The use of network-type scheduling techniques had also expanded, and further growth in the use of network-type schedules was indicated.
A research report submitted to the Civil Engineering department, at the University of the Witwatersrand, in part fulfillment of the requirements for the MSc Civil Engineering degree.
Keywords: Production scheduling; Critical path analysis; Construction industry -- Management; Programming (Mathematics)